Alterations of Gut Microbiome in the Patients With Severe Fever With Thrombocytopenia Syndrome - Xu, Honghai; Wei, Yuanyuan; Ma, Hongqiu; Liu, Yanyan; Zhang, Yalong; Hu, Lifen; Li, Jiabin (Frontiers in Microbiology, 2018)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne infectious disease caused by SFTS virus, and the number of SFTS cases increased year by year in China. Previous studies had indicated that gut microbiome closely associated with human health and diseases, including infection diseases, liver diseases, gastrointestinal diseases and metabolic diseases. The aim of this study is to investigate the alterations and involvements of gut microbial in SFTS patients. We compared the gut microbiome of 26 SFTS patients between 20 health controls using the Illumina MiSeq sequencing platform. Reduced gut microbiota diversity and dramatic shifts of fecal microbial composition in SFTS patients were observed compared with health controls. In the intestinal microbial of SFTS patients, the Lachnospiraceae and Ruminococcaceae which could produce short-chain fatty acids were clearly dropped compared with health people, meanwhile, Sutterella which have anti-inflammation properties were reduced too. On the contrary, some common opportunistic pathogens like Enterococcus and Strepeococcus and endotoxin-producing bacteria Escherichia which could rise the risk of infections were increased in SFTS patients than healthy people, in addition lactate-producing bacteria Lactobacillaceae also significantly increased in SFTS patients. These alterations of gut microbiome in SFTS patients suggest the potential contributions of gut microbial to the pathogenesis of SFTS.